Intrathecal Morphine Plus General Anesthesia in Cardiac Surgery: Effects on Pulmonary Function, Postoperative Analgesia, and Plasma Morphine Concentration - dos Santos, Luciana Moraes (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2009)
OBJECTIVES: To evaluate the effects of intrathecal morphine on pulmonary function, analgesia, and morphine plasma concentrations after cardiac surgery. INTRODUCTION: Lung dysfunction increases morbidity and mortality after cardiac surgery. Regional analgesia may improve pulmonary outcomes by reducing pain, but the occurrence of this benefit remains controversial. METHODS: Forty-two patients were randomized for general anesthesia (control group n=22) or 400 μg of intrathecal morphine followed by general anesthesia (morphine group n=20). Postoperative analgesia was accomplished with an intravenous, patient-controlled morphine pump. Blood gas measurements, forced vital capacity (FVC), forced expiratory volume (FEV), and FVC/FEV ratio were obtained preoperatively, as well as on the first and second postoperative days. Pain at rest, profound inspiration, amount of coughing, morphine solicitation, consumption, and plasma morphine concentration were evaluated for 36 hours postoperatively. Statistical analyses were performed using the repeated measures ANOVA or Mann-Whiney tests (*p<0.05). RESULTS: Both groups experienced reduced FVC postoperatively (3.24 L to 1.38 L in control group; 2.72 L to 1.18 L in morphine FEV(1) (p=0.085), group), with no significant decreases observed between groups. The two groups also exhibited similar results for FEV(1)/FVC (p=0.68) and PaO(2)/FiO(2) ratio (p=0.08). The morphine group reported less pain intensity (evaluated using a visual numeric scale), especially when coughing (18 hours postoperatively: control group= 4.73 and morphine group= 1.80, p=0.001). Cumulative morphine consumption was reduced after 18 hours in the morphine group (control group= 20.14 and morphine group= 14.20 mg, p=0.037). The plasma morphine concentration was also reduced in the morphine group 24 hours after surgery (control group= 15.87 ng.mL(−1) and morphine group= 4.08 ng.mL(−1), p=0.029). CONCLUSIONS: Intrathecal morphine administration did not significantly alter pulmonary function; however, it improved patient analgesia and reduced morphine consumption and morphine plasma concentration.